2005
DOI: 10.1080/00365520510015557
|View full text |Cite
|
Sign up to set email alerts
|

Disseminated tumor cells in the blood of patients with gastric cancer are an independent predictive marker of poor prognosis

Abstract: Detection of DTC in venous blood of gastric cancer patients is an independent predictive marker of poor prognosis and thus could help to define patients for adjuvant therapy with this tumor entity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
32
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 30 publications
1
32
0
Order By: Relevance
“…In most of the studies included in this current analysis, the CTC detection rate was related to the surgical manoeuvres during the surgical removal of excisable cancers, which in turn was initially correlated with poor survival. 18,22 Surgery-related CTC release was also shown in another study, even though postoperative CTC positivity was associated with an improved prognosis. 41 Using the CELLSEARCH Õ system, the CTC detection rate varied between 14% and 55% in 14 nonmetastatic and 27 metastatic patients, respectively (!2 CTCs/ 7.5 ml).…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…In most of the studies included in this current analysis, the CTC detection rate was related to the surgical manoeuvres during the surgical removal of excisable cancers, which in turn was initially correlated with poor survival. 18,22 Surgery-related CTC release was also shown in another study, even though postoperative CTC positivity was associated with an improved prognosis. 41 Using the CELLSEARCH Õ system, the CTC detection rate varied between 14% and 55% in 14 nonmetastatic and 27 metastatic patients, respectively (!2 CTCs/ 7.5 ml).…”
Section: Discussionmentioning
confidence: 98%
“…3,6,16,22 It has not been possible to assess their relative importance and clinical significance because the data available are currently so limited. Most of the studies published in the literature reported positive results (i.e.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The presence of CTCs in circulation suggests not only a high risk of tumor recurrence, but also an unfavorable clinical outcome even in the early stages of GC [20]. The prognostic impact of CTCs in GC has been reported in several studies [21][22][23][24][25][26][27]. The sensitivity of RT-PCR CTC detection was superior to the other less commonly used cytological detection methods involving fluorescence-activated cell sorting (FACS), immunohistochemistry (IHC), and immunocytochemistry (ICC) [20].…”
Section: Gastric Cancer (Gc)mentioning
confidence: 99%